Analysis of the Potential of Billboard Waqf Product Development in Yogyakarta City - Ridwan, Muhammad Yusuf; Fairuz, Khansa; Dwi, Fira (Journal of Islamic Economic Scholar, 2020)
Today, the management of waqf in Indonesia is not only concerned with the scope of consumptive waqf products. As an effort to optimize waqf assets in Indonesia, other forms of productive distribution have emerged, one of which is cash waqf. The advantage of this form of waqf is that there is flexibility in the allocation of use according to community needs. One form of the use of cash waqf is property leasing. Leasing is one of the most common economic utilization methods that have been used by waqf administrations to use the property represented (Afifi, 1991). One form of property waqf is to make a waqf wall for billboards that can be rented (Musaee, 2013). This form of leasing is in the form of multi-storey building walls, building roofs, and land adjacent to highways for advertising (Mahmoud, 2013). The selection of billboards as a form of distribution of waqf funds aims to increase the benefits of the invested waqf funds and be distributed to those in need. Researchers conducted a case study analysis in the city of Yogyakarta by considering the large number of billboards, namely 271 units (Independent Monitoring Forum, 2018). The method used in writing this paper is descriptive-explanative with a qualitative approach. The data used in this research is secondary data obtained through literature study. This study aims to determine the potential use of billboards for waqf. So, the output of this research will be an analysis of the potential development of billboard waqf products. Furthermore, this research is expected to become a reference for waqf fund channeling agencies in making innovations for the distribution of waqf funds in Indonesia. Thus, the benefits generated in society will be broader. Keywords: billboards, property, infrastructure, productive waqf